(untitled) (World Science, 2021)
The influence of the chosen method of anesthesia on cognitive functions in the postoperative period is investigated in the article. Cognitive status analysis was performed using neuropsychological testing: Frontal Assessment Battery (FAB), short-term mental status assessment scale (Mini-MentalStateExamination - MMSE). The evaluation was performed in 3 stages: on the eve of surgery, 7 days after it and on the 21st day of the postoperative period. Patients were divided into two groups: group k - patients received general anesthesia with narcotic analgesics and benzodiazepines in premedication for 40 minutes, maintenance of anesthesia - sevoflurano - oxygen mixture on a low gas stream. minutes before surgery. Estimation of the depth of analgesia was monitored using ANI (Analgesia Nociception Index, index of analgesia with nociceptive effect), evaluation of the depth of sedation - by BIS (Bispectral index, Bispectral index). Patients in both groups were statistically comparable by gender and age. Given the comparative analysis of changes in neuropsychological testing on the FAB scale, the average in the group using dexmedetomidine increased by 13.3% relative to baseline. After a comparative analysis of neuropsychological testing on the MMSE scale, the indicators in the group using dexmedetomid while in the group with the "classical" method of anesthesia, they did not change significantly. Based on the data obtained, it can be argued that the use of dexmedetomidine, as a component of multimodal analgesia, has a positive effect on the state of cognitive functions in the post-anesthetic period.